Biosynthesis of Streptococcal Cell Walls: N-Acetyl-d-Muramic Acid - Barkulis, S. S. (1967)
Glucose-1-(14)C and acetylglucosamine-1-(14)C were added singly and together with equal amounts of the unlabeled reciprocal to Brain Heart Infusion and used for the culture of Streptococcus pyogenes. The labeling pattern of the rhamnose, glucosamine, and muramic acid in the cell wall supported an intermediary role for acetylglucosamine in providing the C1-C6 moiety of muramic acid. Although radioactivity in the C2-C9 portion of muramic acid suggested that some of the lactyl group (C7-C9) came from glycolytic products, there was also considerable contribution to it from noncarbohydrate sources. Using cell-free extracts, we were unable to demonstrate biosynthesis of acetylmuramic acid, either free or nucleotide-bound, while glycolysis was occurring. The formation of uridine diphosphoacetylmuramic acid has been reported by others who used uridine diphospho-N-acetyl-d-glucosamine, phosphoenolpyruvate, reduced nicotinamide adenine dinucleotide, and reduced nicotinamide adenine dinucleotide phosphate. However, we did not detect the formation of this compound.